OPTIMIZING TELIDSON TREE STRUCTURES/MAXIMISER LES STRUCTURES ARBORESCENTES DE TELIDON - Schabas, Ann H. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF